AKTIVITAS SASTRA DI UNIVERSITAS HALU OLEO (Literature Activity in Halu Oleo University) - NFN Rahmawati; Heksa Biopsi Puji Hastuti; NFN Syaifuddin; NFN Mulyadi (Kandai, 2021)
This study aimed to describe the literary activities carried out at Halu Oleo University (UHO) Kendari in the perspective of the sociology of literature by Pierre Bourdieu. This research is a qualitative descriptive study. Research data were information about literary activities at UHO obtained through questionnaires, interviews, note-taking, and literature studies. The informants' answers from the interviews in the research instrument were recorded. Literature study was used to obtain as much data as possible from relevant books or writings. Data from interviews, recordings, and literature studies were described and then classified according to the research problem. The results showed that literary activities that are often held at UHO include various literary activities that were packaged in an activity. In it, various literary activities were carried out, such as the Gerbang Lastra (Lastra Gate), Pentas Arena (Arena Performances), Pekan Sastra (Literature Week), Hibah Sastra (Literature Grants), Lomba Seni dan Pameran Karya (Lensa) (Art Competitions and Work Exhibitions), and so on. Student organizations that often hold literary activities included the Studio Drama, FKIP UHO, Bengkel Sastra Indonesia (BSI, Indonesian Literature Workshop), Pekerja Puisi Sulawesi Tenggara (Eksis) (Southeast Sulawesi Poetry Worker), Laskar Sastra (Lastra), UK-Seni, Sanggar Katalis, Fista, Himpunan Mahasiswa Jurusan Pendidikan Bahasa Indonesia HMJJPBI (Indonesian Language Education Department Student Association), and Himpunan Mahasiswa Sastra Indonesia (HMSSI) (Indonesian Literature Student Association). Literary activities that were built were born from the correlation between habitus, arena, capital capital, social capital, cultural capital, and symbolic capital. In carrying out literary activities, event organizers are still often constrained by funding, training venues, and secretariat rooms. Funding constraints are overcome by using membership fees, charging competition participants, sponsors, or holding fundraising activities through bazaar activities.Penelitian ini bertujuan mendeskripsikan aktivitas sastra yang dilaksanakan di Universitas Halu Oleo (UHO) Kendari dalam perspektif sosiologi sastra Pierre Bourdieu. Penelitian ini merupakan penelitian deskriptif kualitatif. Data penelitian merupakan informasi mengenai aktivitas sastra di UHO yang diperoleh melalui teknik kuisioner, wawancara, pencatatan, dan studi pustaka. Jawaban informan dari hasil wawancara dalam instrumen penelitian dicatat. Studi pustaka digunakan untuk memperoleh data sebanyak-banyaknya dari buku-buku atau tulisan yang relevan. Data hasil wawancara, pencatatan, dan studi pustaka dideskripsikan kemudian diklasifikasi sesuai dengan permasalahan penelitian. Hasil penelitian menunjukkan bahwa aktivitas sastra yang sering diadakan di UHO meliputi berbagai kegiatan sastra yang dikemas dalam suatu kegiatan. Di dalamnya dilaksanakan berbagai aktivitas sastra, seperti Gerbang Lastra, Pentas Arena, Pekan Sastra, Hibah Sastra, Lomba Seni dan Pameran Karya (Lensa), dan sebagainya. Organisasi kemahasiswaan yang kerap menggelar kegiatan sastra antara lain Studio Drama FKIP UHO, Bengkel Sastra Indonesia (BSI), Pekerja Puisi Sulawesi Tenggara (Eksis), Laskar Sastra (Lastra), UK-Seni, Sanggar Katalis, Fista, Himpunan Mahasiswa Jurusan Pendidikan Bahasa Indonesia HMJJPBI), dan Himpunan Mahasiswa Sastra Indonesia (HMSSI). Aktivitas sastra yang dibangun lahir dari adanya korelasi antara habitus, arena, modal kapital, modal sosial, modal budaya, dan modal simbolik. Dalam menjalankan aktivitas sastra, penyelenggara kegiatan masih sering terkendala dengan pendanaan, tempat latihan, dan ruang sekertariat. Kendala dana diatasi dengan menggunakan iuran anggota, mengenakan biaya pada peserta lomba, sponsor, atau mengadakan kegiatan pencarian dana melalui kegiatan bazar.